Imagining education : educational policy and the labor earnings distribution (2008)
This paper simulates, within a partial equilibrium framework, the scenarios resulting form the implementation of several educational policies. Then, policies are compared according to their hypothetical results in terms of labor earnings inequality, as measured by the Gini coefficient. Results suggest that educational policies which attempt to guarantee medium qualification produce the lowest inequality even if dispersion in schooling years is high. Policies which attempt to raise tertiary education coverage but do not raise high school coverage as well, lead to rising inequality.